PEMANFAATAN PEMROGRAMAN VISUAL SEBAGAI ALTERNATIF PEMBUATAN MEDIA BELAJAR BERBASIS GAME DAN ANIMASI - Gunawan, Dedi; Al Irsyadi, Fatah Yasin (Universitas Muhammadiyah Surakarta, 2016)
Visual programming is the one programming technique in computer Science which aims to give easy understanding in writing code program. The main users of visual programming are students and people who have no experiences in making computer code and lack of computer programming language.Visual programminggives advantages to develop any kind of application software such as game and application related to education. This research was conducted to the teachers who teach Al-Quran for children learning in order to know the benefit of using visualprogramming in terms of creating an animation and game education.Several approach has been applied in this research. The first is surveying the knowledge in computer programming by using questioners. Following that, we provide a training of using visual programming and the last is conduction survey in order to know the progress of learning accuisiton.Based on the questionerâs data,it can be found that visual programming is very useful to introduce computer programming for people who have limited computer background. The data shows that 60% respondent believe that the visual programming is easy to follow, while the rest says it is hard to do. Furthermore, some of the participants are able to create simple education game